STUDENT MANUAL : TESTING A HYDROCARBON REFRIGERANT LEAK DETECTOR WITH ARDUINO NANO AND MQ-2 SENSOR - Akhsan, Ibnu Nur; Wibawa, Basuki (Universitas Pendidikan Indonesia, 2024)
This research aims to address public concerns regarding the use of hydrocarbon refrigerants, which are prone to leakage and have the potential to cause explosions and fires. Therefore, a hydrocarbon refrigerant gas leak detector was developed using the MQ-2 sensor for accurate detection. This device utilizes an Arduino Nano microcontroller to detect the gas. The manufacturing method includes both hardware and software development. The results show that this device is effective in detecting leaks by measuring the PPM (parts per million) values from five sensors, producing 70 buzzer sounds in 20 minutes when 105 grams of hydrocarbon refrigerant is released, and the device tsemperature reaches 30°C. The visual indicator provides